Symmetry Groups of An Hypergeometric Series - Kajihara, Y. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
Structures of symmetries of transformations for Holman-Biedenharn-Louck An hypergeometric series: An terminating balanced ₄F₃ series and An elliptic ₁₀E₉ series are discussed. Namely the description of the invariance groups and the classification all of possible transformations for each types of An hypergeometric series are given. Among them, a ''periodic'' affine Coxeter group which seems to be new in the literature arises as an invariance group for a class of An ₄F₃ series.